APPROVAL OF A HEALTHY LIFESTYLE AMONG FUTURE PRIMARY TEACHERS - Razmolodchikova М.В.; Ryabovol А.В. (Pedagogy of Higher and Secondary Education, 2022)
In the article, an author describes the issue of the day of maintenance of heath which the mortgage of development of harmonious personality and professional qualities of are teachers of initial classes.